Perbandingan Lokasi Kompres Ice Gel antara Dada dan Ketiak terhadap Perubahan Suhu Tubuh Pasien Post Craniotomy di Ruang ICU RSI Sultan Agung Semarang - Fitri Cahyaningrum; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Craniotomy is a medical procedure to open the skull in order to repair and assess damage to the brain, which can cause fever due to thermoregulatory disturbances in the central nervous system. Monitoring the body temperature of post-craniotomy patients is crucial, as hyperthermia can increase the risk of complications. One non-pharmacological therapy to reduce fever is the use of ice gel compresses. This study aims to compare the effect of ice gel compress placement between the chest and armpit on body temperature changes in post-craniotomy patients in the ICU of RSI Sultan Agung Semarang. This research uses a pre-experimental design with a two-group pretest-posttest design, involving 22 respondents selected through total sampling technique. Data were collected using observation sheets, and statistical analysis was performed using the Paired Samples Test. The analysis results showed that the p-value for the chest was 0.867 (p > 0.05) and for the armpit was 0.199 (p > 0.05), indicating no significant difference in body temperature before and after the ice gel compress at both locations in relation to the body temperature changes of post-craniotomy patients. In conclusion, the application of ice gel compresses to the chest and armpit locations did not show a significant effect on reducing body temperature in post-craniotomy patients.